2017
DOI: 10.1016/j.fas.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of active toe movement (AToM) on calf pump function and deep vein thrombosis in patients with acute foot and ankle trauma treated with cast – A prospective randomized study

Abstract: Active toe movement is not a viable strategy for thromboprophylaxis in patients with acute foot and ankle trauma treated with cast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Moreover, the accumulation of coagulation factors leads to the overactivation of the coagulation system, thereby leading to accelerated thrombosis. 8,[12][13][14] In the present study, patients with lower extremity fractures at the age of >60 years were found to have the highest incidence of DVT (6.04%), and this was similar to the findings of Williams et al 7 In the opinion of the present authors, there are more internal diseases in elderly patients, which results in a longer preparation time for surgery and longer preoperative resting time. Moreover, elderly patients often have vascular sclerosis, high blood viscosity, and poor venous valve function, which lead to a high incidence of lower extremity DVT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the accumulation of coagulation factors leads to the overactivation of the coagulation system, thereby leading to accelerated thrombosis. 8,[12][13][14] In the present study, patients with lower extremity fractures at the age of >60 years were found to have the highest incidence of DVT (6.04%), and this was similar to the findings of Williams et al 7 In the opinion of the present authors, there are more internal diseases in elderly patients, which results in a longer preparation time for surgery and longer preoperative resting time. Moreover, elderly patients often have vascular sclerosis, high blood viscosity, and poor venous valve function, which lead to a high incidence of lower extremity DVT.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the accumulation of coagulation factors leads to the overactivation of the coagulation system, thereby leading to accelerated thrombosis. 8,12 14…”
Section: Discussionmentioning
confidence: 99%
“…However, none met the inclusion criteria of our systematic review. 11,[37][38][39][40] Second, all the included RCTs in our study performed screening imaging for DVT on their entire participants at various time frames, rather than investigating symptomatic patients only. Although the guidelines do not recommend for systematic screening, 41 the significance of symptomatic and asymptomatic proximal DVT on patients' outcomes has been demonstrated before.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term bed rest leads to reduced muscle pumping, severe local blood ow stagnation, and serious vascular endothelial injury. Moreover, the accumulation of coagulation factors leads to the overactivation of the coagulation system, thereby leading to accelerated thrombosis [9,[13][14][15] . However, once the venous thrombosis of lower extremities is formed, due to changes in the body position or local massage factors, the thrombosis tends to fall off and form fatal PE; it has been reported that 10% of patients with DVT develop fatal PE [16] .…”
Section: Discussionmentioning
confidence: 99%